Small Angle Neutron Scattering Reveals Wood Nanostructural Features in Decay Resistant Chemically Modified Wood - Ibach, Rebecca E.; Plaza, Nayomi Z.; Pingali, Sai Venkatesh (Frontiers in Forests and Global Change, 2022)
While it is known that modifying the hydroxyls in wood can improve the decay resistance; what is often missing in the literature is whether these modifications alter wood nanostructure, and how these changes correlate to the improved decay resistance. Here, we used small angle neutron scattering (SANS) to probe the effects of alkylene oxide modifications on wood nanostructure. Southern pine wood samples were chemically modified to various weight percentage gains (WPG) using four different alkylene oxides: propylene oxide (PO), butylene oxide (BO), epichlorohydrin (EpH) and epoxybutene (EpB). After modification, the samples were water leached for two weeks to remove any unreacted reagents or homopolymers and then equilibrium moisture content (EMC) was determined. Laboratory soil block decay evaluations against the brown rot fungus Gloeophyllum trabeum were performed to determine weight loss and biological efficacy of the modifications. To assist in understanding the mechanism, SANS was used to study samples that were fully immersed in deuterium oxide (D2O). These measurements revealed that the modifications altered the water distribution inside the cell wall, and the most effective modifications reduced the microfibril swelling. Likewise, we observed that these modifications were also able to preserve the microfibril structure even after being subject to 12 weeks of brown rot exposure.